1993
DOI: 10.1080/01431169308904422
|View full text |Cite
|
Sign up to set email alerts
|

Grassland mapping/monitoring of Banni, Kachchh (Gujarat) using remotely-sensed data

Abstract: In India 12.15million ha of land, i.e., 3.7 per cent of the total geographical area, has been recorded as permanent pasture or grazing land. In recent years, the factors responsible for gradual loss of grassland are expanding agriculture, overstocking of domestic animals at a phenomenal rate and improper pasture and grazing land management. However, in an agriculture-based economy, like that of India, a judicious ratio has to be maintained amongst grasslands, croplands and forestlands, in order to obtain optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…3. This phenomenon has previously been observed in the nearby region of Kuch, in Gujarat, where remote sensing reveals a decline of grassland in the wake of julflora growth (Jadhav, Kimothi, and Kandya 1993). 4.…”
Section: Acknowledgmentssupporting
confidence: 66%
“…3. This phenomenon has previously been observed in the nearby region of Kuch, in Gujarat, where remote sensing reveals a decline of grassland in the wake of julflora growth (Jadhav, Kimothi, and Kandya 1993). 4.…”
Section: Acknowledgmentssupporting
confidence: 66%
“…The plant is an aggrasive colonizer, and has invaded large tracts of the grasslands through seed dispersal and animal litter, replacing the existing grass species. The rate of spread in the 1980s was calculated as 2673 ha y !1 (Jadhav et al, 1993). Although the species is fast-growing and has a high value for fuelwood, there is hardly any other benefit from it for the cattle rearers.…”
Section: Management Needsmentioning
confidence: 98%
“…The tree was introduced to Banni in 1961 with the objective of checking the ingress of the salt pan desert, the Great Rann of Kutch, which lies to Banni's north (Kumar et al 2015). Since its introduction Prosopis has spread rapidly, and now occupies over 50% of Banni (Jadhav et al 1993; Pasha et al 2014). In fact, it has been suggested that in 30 years (since the 1960s) afforestation has successfully converted all of Kutch into a Prosopis woodland (Saxena 1993).…”
Section: Introductionmentioning
confidence: 99%